EXPLORING PARENTAL INVOLVEMENT OF THE SEA-GYPSY TRIBE IN THEIR CHILDREN’S ENGLISH LANGUAGE EDUCATION - Dunifa, La (Universitas Islam Sumatera Utara (UISU), 2024)
This study examines the involvement of the Sea-Gypsies tribe in their children’s English education and the factors influencing their participation. The research is guided by two questions: